THE ANTIBACTERIAL ACTIVITY OF BAWANG DAYAK (ELEUTHERINE BULBOSA (MILL.) URB.) FROM CENTRAL KALIMANTAN AGAINST ACNE-CAUSING BACTERIA - NOVARYATIIN, SUSI; ARDHANY, SYAHRIDA DIAN (International Journal of Applied Pharmaceutics, 2019)
Objective: The objective of this research was to investigate the antibacterial activity of bawang dayak from Central Kalimantan against acne-causing bacteria namely Propionibacterium acnes, Staphylococcus epidermidis, and Staphylococcus aureus. Methods: The preliminary phytochemical constituents were qualitatively analyzed. Antibacterial activity of bawang dayak ethanol extract was performed using disc-diffusion technique, with five variations of concentration of 1.25%, 2.5%, 5%, 10%, and 20%. Results: Bawang dayak extract contained flavonoids, alkaloids, saponins, and tannins. The inhibition zones of bawang dayak ethanol extract in five various concentrations (1.25%, 2.5%, 5%, 10%, and 20%) were 7.0±1.3 mm, 8.5±0.6 mm, 9.9±0.3 mm, 11.2±0.1 mm, and 11.9±0.3 mm against P. acnes; 18.8±3.3 mm, 21.9±3.3 mm, 20.8±0.6 mm, 22.0±0.2 mm, and 23.1±0.6 mm against S. epidermidis; and 14.3±3.1 mm, 13.5±0.9 mm, 14.7±1.5 mm, 16.1±1.0 mm, and 20.1±0.6 mm against S. aureus, respectively. Conclusion: This present study showed that bawang dayak ethanol extract was active against all the tested acne-causing bacteria. The highest antibacterial activity was produced by 20% of bawang dayak ethanol extract against S. epidermidis.